Ang Daigdig ko'y ikaw - Reyes, Efren; Poe, Fernando Jr.; Roces, Susan; Keesee, Oscar; FPJ Productions (Firm). ([Place of production not identified] FPJ Productions, 1965)
"Vicky is the spoiled heiress of a multi-millionaire, while Roman is the president and truck driver of Roman's Trucking Corporation. In rebelling against her father's wishes, Vicky and Roman's paths will cross as they journey from Batangas to Baguio, and along the way get to know each other and fall in love with one another."
taken from: https://en.wikipedia.org/wiki/Ang_Daigdig_Ko%27y_Ikaw
Produced by Fernando Poe Jr.; music by Tony Maiguez; cinematography by Sergio Lobo.
Fernando Poe Jr., Susan Roces, Oskar Keesee.
DVD
In Tagalog
Keywords: Comedy; Romance